Coenzyme Q10 and Its Therapeutic Potencies Against COVID-19 and Other Similar Infections: A Molecular Review - Mohammad Fakhrolmobasheri; Mahnaz-Sadat Hosseini; Seyedeh-Ghazal Shahrokh; Zahra Mohammadi; Mohammad-Javad Kahlani; Seyed-Erfan Majidi; Mehrdad Zeinalian (Tabriz University of Medical Sciences, 2023)
Purpose: New lethal coronavirus disease 2019 (COVID-19), currently, has been converted to a disastrous pandemic worldwide. As there has been found no definitive treatment for the infection in this review we focused on molecular aspects of coenzyme Q10 (CoQ10) and possible therapeutic potencies of CoQ10 against COVID-19 and similar infections. Methods: This is a narrative review in which we used some authentic resources including PubMed, ISI, Scopus, Science Direct, Cochrane, and some preprint databases, the molecular aspects of CoQ10 effects, regarding to the COVID-19 pathogenesis, have been analyzed and discussed. Results: CoQ10 is an essential cofactor in the electron transport chain of the phosphorylative oxidation system. It is a powerful lipophilic antioxidant, anti-apoptotic, immunomodulatory and anti-inflammatory supplement which has been tested for the management and prevention of a variety of diseases particularly diseases with inflammatory pathogenesis. CoQ10 is a strong anti-inflammatory agent which can reduce tumor necrosis factor-α (TNF-α), interleukin (IL)- 6, C-reactive protein (CRP), and other inflammatory cytokines. The cardio-protective role of CoQ10 in improving viral myocarditis and drug induced cardiotoxicity has been determined in different studies. CoQ10 could also improve the interference in the RAS system caused by COVID-19 through exerting anti-Angiotensin II effects and decreasing oxidative stress. CoQ10 passes easily through blood-brain barrier (BBB). As a neuroprotective agent CoQ10 can reduce oxidative stress and modulate the immunologic reactions. These properties may help to reduce CNS inflammation and prevent BBB damage and neuronal apoptosis in COVID-19 patients. Conclusion: CoQ10 supplementation may prevent the COVID-19-induced morbidities with a potential protective role against the deleterious consequences of the disease, further clinical evaluations are encouraged.